Youth unemployment: Déjà Vu? - David N.F. Bell; David G. Blanchflower (Institute for the Study of Labor (IZA), 2010)
This paper reviews current issues in youth labour markets in developed countries. It argues that young people aged 16-25 have been particularly hard hit during the current recession. Using the USA and UK as cast studies, it analyses both causes and effects of youth unemployment using micro-data. It argues that there is convincing evidence that the young are particularly susceptible to the negative effects of spells of unemployment well after their initial experience of worklessness. Because the current youth cohort is relatively large, the longer-term outlook for youth unemployment is quite good, but there is a strong case for policy intervention now to address the difficulties that the current cohort is having in finding access to work.
Keywords: J01; J11; J21; J23; J38; J64; 330; Youth unemployment; scarring; ethnic crime; health; life satisfaction; wages; ALMP; Jugendarbeitslosigkeit; Wirtschaftskrise; Soziale Folgen; Arbeitsmarktpolitik; Großbritannien; USA